Trajetórias de Jovens Mulheres LBT: Memórias de (Des)acolhimento Institucional, violências e resistências - Caires, Rute (Universidade Federal de São Carlos, 2023)
This work was based on studies on the human condition in contemporary times and has as its theme the violence suffered by people who are touched by the categories of inequalities, in particular, gender, race, class and sexuality. The aim of this research was to understand how young lesbian, bisexual and transgender (LBT) women experience the processes of institutional reception in shelters for children and teens. Specifically, bearing in mind that these women are now adults and are no longer in these shelters, it intended to: a) analyze the memory narratives of the experiences lived by these young women in the shelters, seeking to identify processes, actions and discourses of resistance and overcoming the possible violence suffered during his life; and b) analyze how the period of institutional sheltering affected the way these young women have built their identities and affective and social relationships after leaving the institution. The theoretical-methodological approach was Oral History. Interviews were held with 03 young LBT women who were institutionally sheltered for having their rights violated and who left the shelters upon reaching the legal age of eighteen. The results of the analyzes of the three interviews carried out reinforced the perspective of the constant violation of the basic rights of the young women participating in the research, marked by various types of violence and negligence that were enhanced in the intersectionality of the categories of inequalities present in their lives. It is therefore concluded how necessary it is to analyze the categories of inequalities in an inseparable way, since the narrators' memories highlight issues related to their classes, sexualities, gender, ages and their races; and they pointed out how these categories meet and overlap in their experiences of abandonment and violence. Although the host system is fundamental for the protection of the rights of the young women interviewed, specific training is needed for the professionals, in order to instruct them on how respect for diversity is part of guaranteeing the rights, above all, for the purpose of ending violences.
Trajectories of young LBT women: violence, resistance and memories of institutional (un)welcome.
Keywords: Acolhimento institucional; Mulheres LBT; Interseccionalidade; Juventudes; Condição humana; Institutional hosting; LBT women; Intersectionality; Youths; Human condition; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS